The Development Enviromental Literacy Media Learning for Elementary School Student - Gusti Izhar; Kristi Wardani; Novian Kharisma Nugraha (Journal of Innovation in Educational and Cultural Research, 2022)
Developing environmental literacy is a significant challenge for Indonesian education. A solid environmental caring character embedded in students can occur due to the success of environmental literacy education, so it is expected that students have a good understanding of the environment. The research aims to produce android-based mobile learning media about environmental literacy in elementary school thematic learning and test the feasibility of android-based mobile learning media developed. This research using research and development (RD) methods, has stages: 1) Analyze, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. Research place in SD Negeri 2 Pagedangan. Research data is processed using instruments. Data analysis techniques are carried out in a quantitative descriptive way. Media eligibility is based on material and media experts' assessments. The results showed that the resulting android-based mobile learning media was worth using with an average score of 3.42 with an "Excellent" criterion for the assessment of mobile learning media in terms of material, and an average score of 3.67 with the criteria "Excellent" for mobile learning media assessment in terms of media. In addition, the average score of student response after using the media is 3.58 with the criteria "Excellent".